(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
Abstract: This article explores some of the key issues in contemporary literature, including representation and identity, literary value and the canon, and the role of technology. It examines debates over cultural appropriation, the right to tell certain stories, and the demand for literature that reflects marginalized voices. The article also considers the challenges posed by the reevaluation of the traditional canon, the role of literary prizes and awards, and the impact of technology on reading and writing. Overall, it argues that these issues offer opportunities for growth and innovation in the literary world, and that by engaging with them, we can create a more inclusive and dynamic literary landscape for the 21st century.